PROGRAM PENGABDIAN KEPADA MASYARAKAT: OPTIMASI PENGGUNAAN ARTIFICIAL INTELIGENT DAN PENCEGAHAN ADIKSI DIGITAL - Muhammad Farras Ma’ruf; Ahmad Fauzi; Andrey Gustaph Setiawan; Defri Salsabila Oktaviani; Desi Sihamita; Luki Handoko; Risa Nur Aisiyah; Abu Khalid Rivai; Mardiyanto (Abdi Jurnal Publikasi, 2026)
The Industrial Revolution 4.0 has brought digital transformation that drives a shift from automated systems toward interconnected intelligent systems. In this context, Generative Artificial Intelligence (Gen AI) plays a significant role across various sectors, including education, through its ability to process multiple data types and deliver rapid analysis. Although Gen AI has been widely utilized by academic communities, its application in the learning process requires careful supervision. A study conducted by Kosmyna et al. found that students who continuously rely on Gen AI for problem-solving in learning experience a cumulative decline in their learning abilities. Based on these findings, a community service initiative was conducted at SMP Putra Pertiwi using two main approaches: first, providing counseling to students and educators regarding the negative impacts of uncontrolled Gen AI usage; second, designing a Gen AI-based system blueprint that continues to promote effective learning while granting schools full control over the management of learning resource access. This initiative is expected to serve as a model for the responsible implementation of AI technology in educational environments.